Hormonal assessment in women with polycystic ovary syndrome in Tikrit city - Mossa M. Marbut; Nada Yahya Awwad; May N. Yousif; Muneif S. Ahmed (Journal of Madenat Alelem University College, 2019)
Polycystic ovarian disease (PCOS) is probably the most prevalent endocrinological disorder affecting females and is the most common cause of menstrual disturbance during the reproductive age. It is characterized by polycystic ovaries on ultrasound and/or clinical and biochemical signs and symptoms of hyperandrogenism and/or oligo- anovulation. Therefore, this study was designed to determine relationship among LH/FSH ratio, BMI and the clinical profile of females suffering from PCOS. Methods: Blood samples were taken from 90 subjects (60 patients with PCOs and 30 normal healthy women as controls) after getting informed consent for hormone profile (FSH and LH) by ELISA kit of Kamiya Biomedical company. Body Mass index (BMI) and Ultra-sonogram related findings of polycystic ovarian syndrome patients were recorded. Result: There are significant elevations in the concentration of FSH and LH in PCOs patients as compare with normal healthy non pregnant women, (p≤ 0.01). Moreover, there is significant increase in the concentration of serum testosterone of patients with PCOs as compare with control women, (p≤ 0.01). Also, there is significant increase in the concentration of prolactin of patients with PCOs as compare with control women, (p≤ 0.01). However, there is significant reduction in the concentration of progesterone of patients with PCOs as compare with control women, (p≤ 0.01). Conclusion: LH and FSH were significantly correlated with obesity and infertility in PCOs patients.